Superimposed topographic and chemical cues synergistically guide neurite outgrowth - Kundu, Arnab (2013)
Guidance of neuronal extensions is a complex process essential for linking neurons into complex functional networks underlying the workings of the neural system. Decades of research have suggested the ability of neuronal growth cones to integrate multiple types of cues during the extension process, but also have raised numerous still unanswered questions about synergy or antagonism between the superimposed chemical and mechanical signaling inputs. In this study, using a novel microfabricated analysis platform, we investigate the response of primary mouse embryonic hippocampal neurons to superimposed topographic and soluble chemical cues. We find that an optimal spatial frequency of topographic cues exists, maximizing the precision of the neurite extension. This optimal frequency can help the extending neurites navigate a topographically complex environment, providing pronounced directional selectivity. We also demonstrate that this cue can synergistically enhance attractive and suppress repulsive guidance by the bi-functional soluble cue Netrin-1, and eliminate the repulsive guidance by a chemorepellent Semaphorin3A (Sema3A). These results suggest that topographic cues can provide optimal periodic input into the guidance signaling processes involved in growth cone chemoattraction and can synergistically interact with chemical gradients of soluble guidance cues, shedding light on complex events accompanying the development of the functional nervous system.